Household income is associated with food and nutrient intake in Japanese schoolchildren, especially on days without school lunch. Issue 16 (30th August 2017) - Murayama, Nobuko; Ishida, Hiromi; Yamamoto, Taeko; Hazano, Sayaka; Nakanishi, Akemi; Arai, Yumi; Nozue, Miho; Yoshioka, Yukiko; Saito, Saori; Abe, Aya
Abstract: Objective: The present study aimed to examine the association between household income and the intake of foods and nutrients by Japanese schoolchildren, and any differences between days with and without school lunch. Design: This was a cross-sectional study. Children, with the support of their parents, kept dietary records with photographs for 4 d (2 d with school lunch and 2 d without). The socio-economic status of each family was obtained from a questionnaire completed by the parents. Setting: Japan. Subjects: All students in 5th grade (10–11 years old) at nineteen schools in four prefectures and their parents (1447 pairs of students and parents) were invited to take part in the study; 836 pairs of complete data sets were analysed. Results: The average results of four days of dietary records showed that lower income level was associated with a lower intake of fish/shellfish, green vegetables and sugar at the food group level, a lower intake of protein and several micronutrients, and a higher energy intake from carbohydrates at the nutrient level among the children. These associations between income and food/nutrient intake were not significant on days with school lunches, but were significant on days without school lunch. Conclusions: Our study confirmed an association between household income and the amount of foods and nutrients consumed by Japanese schoolchildren, and suggested that school lunches play a role in reducing disparities in the diets of children from households with various incomes.